(untitled) (Revista de História da UEG (REVHIST), 2023)
This paper proposes to address the matrices of ultramontane Catholic thought, that is, the current most lined to papal positions. From this, aspire to problematize the authors of greater influence on the O Apostolo journal, to understand the content of its editorial orientation in a context of crisis of the Catholic Church. Furthermore, aims to analyze the repercussion of the book Zuavo da Liberdade (1872) by Antonio Secioso Moreira de Sá (1833-1910) in the press of the period. From that, it is possible to identify the broad dispute in which the various groups were involved in the final decades of the Brazilian Empire. As well as the conservative Catholic reaction to the doctrines of the 19th century, heirs of the French Revolution of 1789. Keywords: Brazil Empire. Catholic Church. Ultramontanism.